The Role of Social Media Platforms like TikTok and Instagram in Informal Language and Cultural Learning - Windo Dicky Irawan; Clara Mendes; Livia Alves (Yayasan Adra Karima Hubbi, 2025)
Background. Social media platforms, particularly TikTok and Instagram, have emerged as powerful tools for informal language and cultural learning in recent years. These platforms facilitate real-time, interactive content sharing, creating a dynamic environment for users to engage with various languages and cultures. Purpose. This research aims to investigate the impact of TikTok and Instagram on language acquisition and cultural understanding among users, particularly focusing on their educational potential. Method. The study employs a qualitative research approach, using content analysis of popular educational videos on both platforms. In-depth interviews with users from diverse linguistic and cultural backgrounds were also conducted to explore personal experiences and learning outcomes. Results. The findings suggest that TikTok and Instagram significantly contribute to informal language learning, offering learners access to authentic content, native speakers, and cultural expressions. Additionally, the study highlights the role of visual and interactive elements in enhancing comprehension and retention. Conclusion. In conclusion, social media platforms, while not substitutes for formal education, serve as valuable supplemental tools for language and cultural learning.